De capa a capa : experiências de leitura com estudantes da educação de jovens e adultos - Agliardi, Delcio Antônio (My University, 2016)
This doctoral dissertation aims at investigating what is the extent and influence of the reading policy destined to young people and adults from the Collections of the National Program Libraries in School (Acervos do Programa Nacional Biblioteca da Escola – PNBE), in order to understand how the reading experience takes place, how new readers are formed and how taste for reading takes place. The study is structured on three thematic lines of thought: the reading experience, the cycle of the educational policy for literary reading, and the school library in a historical moment in which Education for Young Adults and Adults (Educação de Jovens e Adultos – EJA) became a teaching modality in Basic Education. Empiric data were built by means of an action research, developed with free participation of students from EJA groups at an Elementary school, located in Caxias do Sul, an average-sized city in the hinterland of Rio Grande do Sul. Choosing action research as the methodology has the purpose of giving the researcher and the group of participants the means to face the research problem in the relationship with the theoretical references and the analysis of the participants’ situations. Literary collections of the PBNE sent to public schools in the country who answer the Senso Escolar (School Survey) annually are taken as the start point for the analysis of the cycle of reading educational policy. It is theoretically supported with the reader being the one who commands the reading and not the book, the need for mediation to form the reader, and reading in the school environment commanded by the syllabus, which requires school library to have activities aimed at the syllabus, a situation that interferes directly on reading for pleasure and forming a reader for literature. The evidence found – and built by action-research, is analyzed and interpreted interdisciplinarily, from theoretical contributions by Ball (2011, 2013), Manguel (1997, 2006), Thiollent (2011), Chartier (1996, 2001), Ramos (2013), and Darnton (1986, 2010). This investigation has its origin in the conviction that Human Sciences and Education are by virtue on a stress axis between theories and practices and one mobilizes and unleashes the other, causing knowledge to advance. That is why a proposal is presented – a contribution to reading history and public policies on reading – which articulates theoretical and practical knowledge, as a reply to current challenges towards incentive of literate culture in the country. The results show that reading history is the history of each reader. Practice of sending literary books to school is an old one and, not connected with mediation projects, it is potential reading, which produces low impact on the experience of reading. School library functions are still associated with demands of the syllabus, which are far away from reading for pleasure. However, the experience of reading changes the person’s self-development path.
Esta tese tem como objetivo investigar o alcance e a influência da política de leitura destinada às pessoas jovens e adultas a partir do acervo do Programa Nacional Biblioteca da Escola (PNBE), a fim de compreender como se dá a experiência de ler, a formação de novos leitores e do gosto pela leitura. Se estrutura a partir de três eixos temáticos de reflexão: a experiência de ler, o ciclo de política (Apêndice 2) educativa de leitura literária e a biblioteca da escola, em um momento histórico em que a Educação de Jovens e Adultos (EJA) passou a ser uma das modalidade de ensino da Educação Básica. Os dados empíricos foram construídos por intermédio de pesquisa-ação, desenvolvida com a participação livre de alunos de turmas da EJA de uma escola de Ensino Fundamental, localizada em Caxias do Sul, cidade de porte médio do interior do Rio Grande do Sul. A escolha da metodologia pesquisa-ação tem o propósito de dar ao pesquisador e ao grupo de participantes os meios para enfrentar o problema de pesquisa na relação com o quadro de referência teórica e de análise das situações dos participantes. Os acervos literários do PBNE enviados a todas as escolas públicas do País, que respondem anualmente o Senso Escolar, são tomados como ponto de partida para a análise do ciclo de política educativa de leitura. Apresenta sustentação teórica de que o leitor é quem comanda a leitura e não o livro, a necessidade da mediação para a formação do leitor e a leitura no ambiente escolar, comandada pelo currículo, exige da biblioteca escolar atividades voltadas aos conteúdos, situação que interfere diretamente na leitura de fruição e na formação do leitor de literatura. Os achados de campo, construídos pela pesquisa-ação, são analisados e interpretados, de forma interdisciplinar, pela contribuição teórica de Ball (2011, 2013), Manguel (1997, 2006), Thiollent (2011), Chartier (1996, 2001), Ramos (2013), Darnton (1986, 2010). A presente investigação decorre da convicção de que as Ciências Humanas e da Educação estão por inerência num eixo de tensão entre as teorias e as práticas e umas mobilizam e desencadeiam as outras, fazendo avançar o conhecimento. Por isso é apresentada uma proposta - uma contribuição à história de leitura e à política pública de leitura - que articula conhecimentos teóricos e práticos, para responder ao desafio atual do incentivo à cultura letrada no País. Os resultados mostram que a história de leitura é a história de cada um de seus leitores. A prática de envio de livros literários às escolas é antiga, e desvinculada de projetos de mediação, produz baixo impacto na experiência de leitura. As funções da biblioteca escolar ainda se associam às demandas do currículo, as quais se mantêm distantes da leitura de fruição. No entanto, a experiência de ler, pode mudar o percurso da autoformação da pessoa.
Keywords: Incentivo à leitura; Leitura - História; Bibliotecas escolares; Educação de adultos; Programa Nacional Biblioteca da Escola (Brasil); Reading promotion; Reading - History; School libraries; Elementary education of adults; Programa Nacional Biblioteca da Escola (Brazil)